The effect of good corporate governance mechanism and leverage on the level of accounting conservatism - Habiba Habiba (The Indonesian Accounting Review, 2016)
Accounting conservatism is a condition where a company acknowledges the debts and costs more quickly, but on the other hand, the company acknowledges the income and assets more slowly. Some factors that can affect the accounting conservatism are stan-dards changes, corporate governance, and so forth. The purpose of this study is to analyze the effect occurring on the variable of accounting conservatism when using comprehensive income and income for the current year in manufacturing companies listed on the Indonesian Stock Exchange in 2012 and 2013. The variables studied are institutional ownership, managerial ownership, the existence of audit committee, the number of audit committee meetings, and leverage. The statistical method used in this study is multiple regression analysis. The results of this study indicate that institu-tional ownership, managerial ownership, and the number of audit committee meetings do not have significant effect on accounting conservatism when using comprehensive income and income for the current year, but the variables of the existence of audit committee and leverage have significant effect on accounting conservatism when using comprehensive income and income for current the year.